2008
DOI: 10.1016/j.dza.2008.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone mediates electroacupuncture-produced anti-edema in a rat model of inflammation

Abstract: Background: Electroacupuncture (EA) has been reported to produce anti-edema and antihyperalgesia effects on inflammatory disease. However, the mechanisms are not clear. The present study investigated the biochemical mechanisms of EA anti-inflammation in a rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…The SNS also activates the HPA axis, stimulating cortisol release [150,152]. As previous mentioned, corticosterone inhibits cytokines, prostaglandin and cox-2, thereby blocking inflammation in rats [151].…”
Section: The Role Of the Endocannabinoid System In Dry Needling-mediamentioning
confidence: 95%
See 1 more Smart Citation
“…The SNS also activates the HPA axis, stimulating cortisol release [150,152]. As previous mentioned, corticosterone inhibits cytokines, prostaglandin and cox-2, thereby blocking inflammation in rats [151].…”
Section: The Role Of the Endocannabinoid System In Dry Needling-mediamentioning
confidence: 95%
“…Following an injection of CFA, EDN was able to control the resulting edema by stimulating a 10-fold increase in corticosterone. When corticosterone receptors were chemically blocked, however, the anti-inflammatory effects of DN were lost [152].…”
Section: Stimulation Of the Neuroendocrine System Via Dry Needlingmentioning
confidence: 99%
“…Accumulative evidence demonstrates that EA significantly inhibits paw inflammation and hyperalgesia in a rat model [1214]. However, it has been reported that EA may produce differential effects under healthy and pathological conditions [15].…”
Section: Introductionmentioning
confidence: 99%
“…This antiedema effect was eradicated in animals given an adrenalectomy (ADX) and in those pretreated with a corticosterone antagonist RU486, 34,35 but neither treatment blocked the antihyperalgesia effect of EA. (2) At the pituitary level, EA significantly increased plasma adrenocorticotropic hormone (ACTH) levels, while the ACTH receptor antagonist ACTH (1124) blocked EA antiedema but not EA antihyperalgesia (unpublished data).…”
Section: The Hormonal Pathwaymentioning
confidence: 99%
“…34,35 Pharmacologic studies showed that EA antihyperalgesia is mediated by mu and delta but not kappa opioid receptors. 36 Studies also show that lesioning of the G-protein-coupled receptor by pertussis toxin blocks EA antihyperalgesia.…”
Section: The Neural Pathwaymentioning
confidence: 99%